Praktik Jual Beli Gigi Hiu Megalodon (Gigi Purba) dalam Perspektif Etika Bisnis Islam - Moh Ramdhan Rizalussani; Neneng Nurhasanah; Popon Srisusilawati (UNISBA Press, 2023)
Abstract. Megalodon is a huge shark(Otodus Megalodon) it is now thought to have become extinct, between about 15 and 2.6 million years ago, during the middle Miocene and Pliocene epochs. Buying and selling denotes the action of one activity, namely that of a seller and a buyer. So in this case there was a sale and purchase transaction that brought legal consequences. In this study, there were several problems that were not carried out in this buying and selling transaction, especially in terms of Islamic business ethics which should be a reference for fellow Muslims. This study aims to determine Islamic business ethics in buying and selling ancient goods, the practice of buying and selling Megalodon Shark Teeth in Gunung Sungging Village, Kec. Surade Kab.Sukabumi and find out the review of Islamic business ethics on the buying and selling of megalodon shark teeth in Kp. Cilutung Village. sungging mountain. The method used is descriptive qualitative, using an empirical approach. The type of data in this study uses field data with primary and secondary data sources. Data collection techniques used in this study were observation, interviews, literature studies, and documentation. The results of this study conclude that (1) Islamic business ethics in buying and selling ancient objects must pay attention to the following principles: a. Unity b. Balance, c. Free will, harming others, d. Responsibility. e. Truth: virtue and honesty (truth, goodness, honesty). (2) The practice of buying and selling Megalodon shark teeth at kp.cilutung contains violations in terms of mining as well as in terms of buying and selling: a. Mining destroys the environment. b. Selling to middlemen c. There are attempts to trick sellers or buyers by making fake shark teeth. d. How to pay e. The sale violated the provisions of the 1945 Constitution No. 11 of 2010 which contained Cultural Conservation. (3) Based on the review of Islamic business ethics regarding the sale and purchase of Megalodon shark teeth, seen from the madiyah and adabiyah aspects, it does not comply with/violates the principles of Islamic business ethics, namely: a. The principle of balance, where there is an element of fraud in the sale and purchase. b. The principle of responsibility is because it is not in accordance with ethics in Islam, in mining practices it does not pay attention to the impacts that arise, without thinking about the impacts around it Abstrak. Megalodon adalah hiu besar (Otodus Megalodon) kini dianggap telah punah, antara sekitar 15 dan 2,6 juta tahun yang lalu, selama zaman Miosen tengah dan Pliosen.Jual beli menunjukkan adanya perbuatan dalam satu kegiatan, yaitu pihak penjual dan pembeli. Maka dalam hal ini terjadilah transaksi jual beli yang mendatangkan akibat hukum. Dalam penelitian ini ada beberapa permasalahan yang tidak dilaksanakan dalam transaksi jual beli ini terlebih dalam hal etika bisnis islam yang seharusnya menjadi acuan bagi sesama muslim. Penelitian ini bertujuan untuk mengetahui etika bisnis islam dalam jual beli barang purba, praktik Jual Beli Gigi Hiu Megalodon di Desa Gunung Sungging Kec. Surade Kab.Sukabumi dan mengetahui tinjauan etika bisnis islam terhadap jual beli gigi hiu megalodon di Kp. Cilutung Desa. Gunung sungging. Metode yang digunakan adalah kualitatif deskriptif, menggunakan pendekatan empiris. Jenis data dalam penelitian ini menggunakan data lapangan dengan sumber data primer dan sekunder. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, interview, studi literatur, dan dokumentasi. Hasil penelitian ini menyimpulkan bahwa (1) Etika bisnis islam dalam jual beli benda purba harus memperhatikan prinsip-prinsip sebagai berikut: a. Kesatuan b. Keseimbangan, c. Kehendak bebas, merugikan orang lain, d. Tanggung jawab. e. Kebenaran: kebajikan dan kejujuran (truth, goodness, honesty). (2) Praktik jual beli gigi hiu Megalodon di kp.cilutung terdapat pelanggaran dari segi penambangan maupun dari segi jual belinya: a. Dalam penambangan merusak lingkungan. b. Menjual kepada tengkulak c. Adanya upaya mengelabui penjual atau pembeli dengan cara membuat gigi hiu palsu. d. Cara pembayaran nya e. Penjualannya melanggar aturan UUD 1945 No.11 Tahun 2010 yang berisikan tentang Cagar Budaya. (3) Berdasarkan tinjauan etika bisnis islam terhadap jual beli gigi hiu Megalodon tersebut di lihat dari aspek madiyah dan adabiyah belum sesuai/melanggar prinsip-prinsip etika bisnis islam yaitu: a.Prinsip keseimbangan, dimana ada unsur penipuan dalam jual beli tersebut. b. Prinsip tanggung jawab karena belum sesuai dengan etika dalam Islam, pada praktik penambangan nya tidak memperhatikan dampak yang timbul, tanpa memikirkan dampak di sekitarnya